Towards Effective Pastoral Caregiving within Contemporary Post-Colonial Praxis in Africa: A Discernment of Care Needs for ‘Now’ and ‘Intervention’ Propositions - Magezi, Vhumani (Religions, 2024)
Post-colonial Africa and its attendant challenges, including disillusionment during democratic dispensation and racial tensions among black and white people, constitute a problem that calls for interventions from all social actors. Theology, especially pastoral care, is challenged to broaden its vision and focus on health, healing, and human flourishing by adopting a public dimension. Thus, public pastoral care can emerge as a critical approach through which to make a meaningful contribution to fostering holistic personal care. This assumption prompts an examination of the place and role of pastoral care as a science and art of fostering social health and well-being. Public pastoral care practices are used to encourage, promote, and foster ‘coexistence’ and ‘being with’ other people in the same geographical spaces where tension and disillusionment exist. Using the South African lens, this article aims to pastorally address challenges emerging from post-colonial African public contexts by developing a public pastoral care approach. Pastoral care principles of empowerment care, prevention care, conversational care, and care by being with the other in shared spaces of coexistence are proposed.